Increased absorption and use of nutrients induced by Si is an indicator for tolerance to water deficit in a common bean cultivar cultivated in the field with and without application of K - Teixeira, Gelza Carliane Marques; Gonzalez-Porras, Carlos Vital; Messias Ferreira, Patrícia; Prado, Renato De Mello; Silva Oliveira, Kamilla; Carvalho, Lívia Tálita da Silva; Palaretti, Luiz Fabiano (Frontiers in Plant Science, 2024)
Reduced water content in the soil triggers physiological, biochemical, and morphological damage to plants, aggravated by nutritional deficiency. One possible strategy to mitigate this damage comprises the use of silicon (Si). This study investigated whether Si can mitigate the damage caused by water deficit through nutritional mechanisms in bean plants grown under field conditions. Furthermore, it investigated whether its effectiveness is influenced by water availability in the soil and the Si dose supplied. Therefore, two split-plot experiments were carried out: with and without K supply. In both experiments, the treatments comprised a 3x4 factorial scheme. Treatments included three water regimes: 80% (no water deficit), 60% (moderate water deficit), and 40% (severe water deficit) of the soil's water retention capacity. Moreover, they comprised four doses of Si supplied via fertigation: 0, 4, 8, and 12 kg ha -1 , arranged in a randomized block design with four replications. The appropriate dose of Si to be applied increased with the severity of the water deficit, with the recommended dose being 6, 7, and 8 kg ha -1 of Si for adequate water conditions and moderate and severe water deficit, respectively.